DEVELOPMENTS IN SELF-EFFICACY AT THE ELEMENTARY SCHOOL LEVEL - M. Luthfi Oktarianto; Sa'dun Akbar; Siti Mas'ula; Dinik Hanisvana; Rifqi Al Farizza (Jurnal Cakrawala Pendas, 2024)
Self-efficacy, or an individual's belief in their ability to accomplish tasks, plays a crucial role in academic success, particularly at the primary education level. This study employed a Systematic Literature Review (SLR) methodology to analyze empirical studies from the past five years (2019-2024) focusing on the impact of self-efficacy on primary school students. Literature searches were conducted across three major databases: Google Scholar, SINTA, and Scopus, yielding 213 articles, which were subsequently screened to obtain 10 articles meeting the inclusion criteria. The analysis process involved three-stage thematic coding: open coding, axial coding, and selective coding, followed by validation through researcher triangulation and member checking. This study explored the impacts of high and low self-efficacy on students' academic performance and identified factors influencing self-efficacy formation, such as family support, teaching quality, school environment, and social interactions. The findings revealed that high self-efficacy positively correlates with better academic achievement, active learning engagement, and resilience in facing academic challenges, while low self-efficacy negatively impacts students' participation in academic activities and learning motivation. The analysis also uncovered the critical role of success experiences, social support, and learning environment quality in shaping students' self-efficacy. Based on these findings, further research is recommended to design more effective interventions for enhancing self-efficacy through social reinforcement and positive academic experiences, supporting students' long-term development across various life aspects.